(untitled) (American Journal of Human Psychology, 2025)
This study focuses on gender differences in English Language anxiety among Moroccan students. A structured questionnaire was employed for data collection by adopting a cross-sectional research design. The respondents comprised 240 university students; the questionnaire included respondents’ demographic data and the English Language Classroom Anxiety Scale (ELCAS). The study aimed to answer three research questions: (1) Does gender significantly influence English language anxiety among Moroccan students? (2) What variables cause male and female students’ English language anxiety? (3) How does English language anxiety affect male and female students’ academic achievement and well-being? The study affirms that the level of English anxiety significantly differs by gender, and the female students had higher English anxiety. Some significantly identified factors include fear of negative evaluation and communication apprehension. The study thus advocates for tailored intervention to address gender-specific language anxiety and promote the student’s academic achievement and well-being.